1992
DOI: 10.1037/0022-006x.60.5.797
|View full text |Cite
|
Sign up to set email alerts
|

Who will relapse? Symptoms of nicotine dependence predict long-term relapse after smoking cessation.

Abstract: Results of a prospective examination (N = 618) of factors associated with smoking relapse are reported. At 1-year follow-up, a modified version of the Fagerstrom Tolerance Questionnaire (Dependence Index; DI) and a measure of craving entered the logistic model (odds ratio of 2.7 [p less than .001]). At Year 2, only the DI entered the model (odds ratio of 2.2 [p less than .001]). The ability of signal detection analysis (SDA) to produce clinically useful decision rules was also examined. At Year 1, SDA produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 9 publications
1
72
0
4
Order By: Relevance
“…In terms of withdrawal, several studies support the intuitive, although experimentally inconsistent (Hughes et al 1990;USDHHS 2000), relationship between the withdrawal syndrome and relapse to smoking (Shiffman 1979;Stitzer and Gross 1988;West et al 1989;Gritz et al 1991;Killen et al 1991Killen et al , 1992Swan et al 1996). It was shown that the severity, duration, and pattern of withdrawal over time were predictive of relapse (Piasecki et al 1998(Piasecki et al , 2000.…”
Section: Introductionmentioning
confidence: 88%
“…In terms of withdrawal, several studies support the intuitive, although experimentally inconsistent (Hughes et al 1990;USDHHS 2000), relationship between the withdrawal syndrome and relapse to smoking (Shiffman 1979;Stitzer and Gross 1988;West et al 1989;Gritz et al 1991;Killen et al 1991Killen et al , 1992Swan et al 1996). It was shown that the severity, duration, and pattern of withdrawal over time were predictive of relapse (Piasecki et al 1998(Piasecki et al , 2000.…”
Section: Introductionmentioning
confidence: 88%
“…Durante las primeras 12 horas sufren un incremento y alcanzan su estado máximo de intensidad alrededor del segundo o tercer día 11,13 . La sintomatología perdura durante la primera semana de la cesación y baja gradualmente algunas semanas después, pero el ansia por fumar puede persistir por meses y a veces años 22 . De hecho, la intensidad de los síntomas asociados al síndrome de abstinencia nicotínica dependerá del tiempo transcurrido desde la última dosis, de la adicción y del grado de dependencia del fumador 13 .…”
Section: Dependencia Nicotínica Psicológicaunclassified
“…Simons & Thase (1992), 53 patients with major depression, Age of onset of first depression, No Barkley et al(1992), 61 adolescents with ADHD, Age of ADHD onset, No Mulhern et al(1992), 49 long-term survivors of childhood leukemia,Age at diagnosis Age at testing, No Wieczorek & Miller (1992), 156 convicted-while-intoxicated offenders, Age at first drink, No Killen et al (1992) (1996), 516 smoking cessation participants, Age of onset of smoking. Number of lifetime quit attempts., No Pianta et al (1996), 110 women in second trimester of pregnancy, Number of T ≥ 65 elevations range: 0 (44%) to 7 (5%), No Newman et al (1996) Grilo et al (1997), 114 adolescent Psychiatric inpatients, Age at first psychiatric contact & psychiatric hospitalization; number of prior psychiatric hospitalizations, No Agras et al (1997), 93 obese women, Age of onset of being overweight and age of onset of binge eating, No…”
Section: Appendix Five-year Systematic Reviewmentioning
confidence: 99%